Clarifications and Question Specificity in Synchronous Social Q&A - Kato, Makoto; White, Ryen W.; Teevan, Jaime; Dumais, Susan (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI 2013), 2013)
Synchronous social question-and-answer (Q&A) systems help people find answer by connecting them with others via instant messaging. To understand how such systems can quickly and effectively establish fruitful connections, we analyze conversations collected from a working enterprise social Q&A system. We show that when askers start with underspecified questions (e.g., “I need help with mail access”), they receive clarification requests, extended dialogs, and poor responses. To address this we are implementing and deploying support within a Q&A system to foster more complete questions, reduce the need for clarification, and benefit both askers and answerers.